Anticancer and immunostimulatory activities of Houttuynia cordata Thunb. Extract and the isolated flavonoids: An in vitro/in vivo investigation - Tran Viet Hung, Phan Nguyen Truong Thang, Nguyen Thi Thu Phuong, Duy Toan Pham, Ha Minh Hien, Duyen Thi My Huynh (Journal of Applied Pharmaceutical Science, 2023)
Houttuynia cordata Thunb. (HC) is a common medicinal herb in Vietnam, which has been utilized for the treatment of various diseases. However, reports on using HC extract and its flavonoid contents for leukemia treatment and immunostimulation are limited. This work investigated the Vietnamese HC extraction processes and its flavonoid content isolation and structure elucidation and evaluated the extract’s long-termed stability, in vitro antileukemia, and in vivo immunostimulatory effects. The maceration method was used for the HC extraction and the liquid chromatography techniques were used for flavonoid isolation. The compounds structures elucidations were performed with infrared spectroscopy, mass spectrometry, and nuclear magnetic resonance spectroscopies. The in vitro and in vivo tests were conducted on K562 and HL60 cell lines using 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyl tetrazolium bromide assay and on the cyclophosphamide (CPA)-induced immunosuppression mice model, respectively. The EtOH 70% solvent was the optimal solvent with the highest extraction efficiency, and the three isolated flavonoids were hyperoside, quercitrin, and afzelin. Physicochemically, the extract was stable for at least 6 months. The HC extract, hyperoside, and quercitrin, at concentrations of 5–100 μg/ml, were nontoxic to the HL60 and K562 cells, indicating that these substances are unsuitable for leukemia treatment. Inversely, HC extract (480 mg/kg), hyperoside (10 mg/kg), and quercitrin (20 mg/kg) significantly increased the CPA-induced mice white blood cell counts, for both neutrophils, lymphocytes, and monocytes, in comparison with the standard drug filgrastim. Conclusively, the HC extract and its isolated flavonoids, hyperoside, and quercitrin could be a potential immunostimulant.
Keywords: Houttuynia cordata Thunb., cytotoxicity, immunostimulant, quercitrin, hyperoside